2005
DOI: 10.2355/isijinternational.45.1721
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mn Content on the Microstructure and Mechanical Properties of Ultrafine Grained C-Mn Steels

Abstract: The effect of Mn content on the microstructure and mechanical properties of two ultrafine grained 0.2%C-Mn steels has been investigated. The ultrafine grained microstructure was produced by use of large strain warm deformation and subsequent annealing. The final microstructure consists of fine cementite particles within an ultrafine grained ferrite matrix. The increase in the Mn content leads to a decrease in the average ferrite grain size (from 1.3 to 0.8 mm for an increase in the Mn content from 0.74 to 1.52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
(24 reference statements)
0
25
0
8
Order By: Relevance
“…it delays carbon flux through austenite. This is of particular importance in the present case because it was observed that cementite is enriched in Mn during the course 47) For these reasons, phase transformation and austenite growth are sluggish at low temperatures and the resulting martensite fraction is small. At higher temperatures, phase transformation is controlled by carbon diffusion, Mn diffusion playing a minor role.…”
Section: Effect Of Holding Temperaturementioning
confidence: 72%
See 2 more Smart Citations
“…it delays carbon flux through austenite. This is of particular importance in the present case because it was observed that cementite is enriched in Mn during the course 47) For these reasons, phase transformation and austenite growth are sluggish at low temperatures and the resulting martensite fraction is small. At higher temperatures, phase transformation is controlled by carbon diffusion, Mn diffusion playing a minor role.…”
Section: Effect Of Holding Temperaturementioning
confidence: 72%
“…Mn is enriched in cementite before intercritical annealing. 47) It was shown in a previous study 27) that the Mn enrichment is inherited by austenite and is clearly visible inside martensite after quenching. From this observation it is clear, that after equilibrium carbon activity is reached throughout the phases at the given intercritical annealing temperature, Mn has to diffuse from austenite to ferrite to reach the final equilibri- Table 1 and text for details.…”
Section: Effect Of Holding Timementioning
confidence: 90%
See 1 more Smart Citation
“…It was shown in a previous project 14) that Mn is advantageous for the production of ultrafine grained ferrite/cementite steels using large strain warm deformation. An increase in Mn content from 0.74 to 1.52 mass%, which is very close to the present investigation composition (0.87 and 1.63 mass%), decreases the average ferrite grain size, increases the fraction of HAGB and leads to a lower aspect ratio.…”
Section: Effect Of Mn Distribution On Microstructure Evolutionmentioning
confidence: 99%
“…Despite the high strength and toughness of the UFG steels they tend to show reduced ductility due to their low work hardening rate. [9][10][11] On the other hand, it seems there is a consensus on the practical ways one can increase ductility of UFG metals. This could be doing by obtaining a final microstructure containing either a dispersion of fine second phase particles or by including a novel mechanism such as TRIP effect in the matrix.…”
Section: Introductionmentioning
confidence: 99%